4D Seismic Inversion and Rock Physic Modeling to Monitor CO2 Injection at Carbon Capture and Storage Project in The Utsira Formation, Sleipner Field, North Sea, Norway - Torus, Bastian; Arista, Kunti Yoga; Wulan, Elta Purnama; Lubis, Muhammad; Herawati, Ida; Pranowo, Waskito (Journal of Earth Energy Engineering, 2023)
Carbon Capture and Storage (CCS) is used at Sleipner Field due to the implementation of a carbon emission tax off the coast of Norway. This project causes the fluid at the Utsira Formation as a reservoir to be replaced by CO2, so the elastic property of the reservoir rock will change. Because of that, the 3D seismic survey was carried out in 1994 (baseline) and re-acquisition in 2001 (monitor) to observe CO2 distribution and changes in rock properties. This study aims to monitor the distribution of CO2 as well as changes in reservoir rock's acoustic and elastic parameters. This research performed the cross-equalization, 4D Seismic Inversion model-based, and rock physics modeling process. From data processing, obtained information that CO2 spreads laterally, then moves to the northeast and does not penetrate the overburden. Also, we get the NRMS value of 0.443068 and the cross-correlation value of 0.907426. 4D Inversion results reveal a change in the reflector at the reservoir zone, as indicated by the velocity pushdown caused for a decrease in seismic velocity owing to CO2. In addition, rock physics modeling provides that changes occur in bulk modulus, Vp, Vs, density, and AI. From the process, there are differences in AI values where the Inversion results show a decrease in AI values of 2.9%, while rock physics modeling shows a 12% reduction.